Subclinical and overt hypothyroidism in pregnancy - adverse neonatal oucomes - Jovanovska Mishevska, Sasha; Pemovska, Gordana; Krstevska, Brankica; Milenkovikj, Tatjana; Bitoska, Iskra; Todorova, Biljana; Adamova, Katerina; Ahmeti, Irfan; Shubeska Stratrova, Slavica; Bozinovska, N (My University, 2018)
Background: Hypothyroidism is associated with an increased risk of adverse maternal and neonatal outcomes, including miscarriage, pre-eclampsia, premature delivery, low birth weight and impaired neuropsychological development of off-spring. Aim: To evaluate the adverse fetal outcomes in women with overt (OH) and subclinical hypothyroidism (SCH) during pregnancy. Material and methods: This retrospective study included 36 women with singleton pregnancies and primary hypothyroidism on levothyroxine replacement, treated at the University Clinic of Endocrinology, diabetes and metabolic disorders. Results: Hypothyroidism was diagnosed prior to the pregnancy in 64% of women, while in 36% hypothyroidism was diagnosed during the pregnancy. SCH was diagnosed in 57%, while 43% had overt hypothyroidism. Optimization of TSH values was observed in the second trimester of pregnancy and mainatined throughout the pregnancy (6.86±1.07 mU/l; 2.49±1.78 mU/l and 1.02±0.53 mU/l, consecutively), with normal fT4 values (11.55±0.63 pmol/l; 13.71±2.75 pmol/l and 13.69±2.87 pmol/l consecutively). Adverse neonatal outcomes in SCH and OH included preterm birth (14%) and low birth weight 14%), with Apgar score of the neonates of 8.83±0.4. Conclusion: The presence of hypothyroidism during pregnancy in our study was associated with adverse neonatal outcomes. Early adequate replacement therapy is especially important in pregnant women presenting with overt hypothyroidism.